2006
DOI: 10.1897/04-584r.1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the applicability of ecotoxicological tests with earthworms, springtails, and plants for the assessment of metals in natural soils

Abstract: The environmental risk assessment of metals in the soil compartment is based mainly on tests performed in Organization for Economic Cooperation and Development (OECD) artificial soil, but ecologically, the use of natural soils would be more relevant. In this contribution, the reproduction and growth of three standard species (an earthworm, a collembolan, and a dicotyledonous plant, respectively) was evaluated in nine natural soils (covering a wide range of pH values, organic matter content, texture, and so on)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 21 publications
4
44
0
2
Order By: Relevance
“…In the case of zinc, this relationship has been substantiated: For the earthworm Eisenia fetida, pH and OM content are most important when tested in a range of artificial soils with different pH values and OM contents (Spurgeon and Hopkin 1996). In the earthworm tests presented here, the correlation between zinc toxicity and soil factors like pH, OC content and CEC was not significant, which might be caused by the fact that the tested soils had very different properties, while in the work cited above only artificial soils with different adjusted pH values and OM contents were tested (Römbke et al 2006a). Therefore, it is not clear whether the availability of zinc indirectly played a role in the effects of zinc on the feeding activity.…”
Section: Influence Of Soil Propertiesmentioning
confidence: 68%
See 3 more Smart Citations
“…In the case of zinc, this relationship has been substantiated: For the earthworm Eisenia fetida, pH and OM content are most important when tested in a range of artificial soils with different pH values and OM contents (Spurgeon and Hopkin 1996). In the earthworm tests presented here, the correlation between zinc toxicity and soil factors like pH, OC content and CEC was not significant, which might be caused by the fact that the tested soils had very different properties, while in the work cited above only artificial soils with different adjusted pH values and OM contents were tested (Römbke et al 2006a). Therefore, it is not clear whether the availability of zinc indirectly played a role in the effects of zinc on the feeding activity.…”
Section: Influence Of Soil Propertiesmentioning
confidence: 68%
“…Test vessels were polystyrene cups with a base area of 110 9 155 mm and a height of 60 mm (Bellaplast 590, Polarcup, Alf, Germany). Five concentrations of zinc nitrate were selected according to literature data (Römbke et al 2006a experiment an amount of 5 g food per 500 g soil DW was mixed into the test soil. After the start of the experiment, food was first provided one day after application of the test item and introduction of the adult worms.…”
Section: Test Performancementioning
confidence: 99%
See 2 more Smart Citations
“…However, properties of some natural soils could be outside the tolerance thresholds for the soil invertebrate test species used in standardized OECD or ISO tests. Römbke et al (2006b) investigated the performance metrics for some of these species, including E. andrei and F. candida in nine uncontaminated natural soils and OECD artificial soil (Table 2). Their studies revealed that reproduction of the test species varied greatly among the soils and was related to differences in soil properties, including texture, OM content, and soil pH (Figure 1).…”
Section: Performance Of Standard Test Species In Uncontaminated Soilsmentioning
confidence: 99%